Design and Build an E-Commerce Application for Building Materials Using the Web-Based Cross Selling Method - Saputri, Indah; Putri, Raissa Amanda; Santoso, Heri (IJISTECH (International Journal of Information System and Technology), 2025)
The Building Materials E-commerce application is a digital platform designed to make it easier for consumers to find and buy building materials. This application is designed to help building stores in reaching more customers by offering a variety of building materials through a web-based platform. By using the cross selling method, the app automatically recommends relevant additional products to customers based on the items they choose, thereby increasing the chances of selling related products. The obstacle faced by Nazir Panglong is that there is no special digitalization touch for the products sold and customers have difficulty finding information related to what goods are sold due to the absence of a product catalog. Therefore, the application of building material ecoomerce was designed to overcome this problem. This application offers easy access for consumers and helps businesses in expanding their market reach, making a positive contribution to the development of the building materials industry in the digital era. This research aims to design and build a web-based e-commerce application that specializes in selling building materials, by integrating the cross-selling method as a sales increase strategy. The type of research method used by the author in this study is the Research and Development research method. By using data collection techniques, namely observation, interviews and literature studies. And the system development method used is RAD (Rapid Application Development) which consists of three phases, namely Requitment Planning, Design Workshop and Implementation. The results of the system trial show that the building materials e-commerce application can be implemented in Nazir Panglong to increase transaction value by offering additional products to customers so as to increase sales of goods and make it easier for customers to purchase products.